PENGEMBANGAN LEMBAR KERJA SISWA BERSTRUKTUR KONSTRUKTIVISME UNTUK MENINGKATKAN KEMAMPUAN PENALARAN ADAPTIF SISWA DI SMA - Dayang Kartika Sari; Dede Suratman; Bistari Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aimed to develop student worksheets with constructivism structure on trigonometry material in SMAN 1 Nanga Taman Sekadau Regency, West Kalimantan Province. The research method used R & D that development by Richey and Klein which include Planning, Production and evaluation. This student worksheets was a Trigonometry student worksheets whose material presentation is developed based on four phases of constructivism. The fourth part of constructivism includes exploration phase, application phase, restructuring phase and reflection phase. Based on the research, it was concluded that the trigonometry student worksheet is valid that was proven through the opinions of three experts and the results of factor analysis.  The factor analysis are the results of student answers on student worksheets, where each item in the factor analysis had a value above r-count, 0.30. The increase of students' adaptive reasoning abilities was seen from the results of the average pretest and post-test calculated using N-Gain amounting to 0.61 with an increase category namely moderate. Keywords: Adaptive reasoning, Constructivism, Student worksheets